Two new synonyms in Neotropical Philonthina (Coleoptera: Staphylinidae) - Chani Posse, Mariana; Salamanca, Jose Manuel Ramírez (Zootaxa, 2019)
As part of an ongoing phylogenetic study on the Neotropical Philonthina (Coleoptera: Staphylinidae) that includes species of Belonuchus Nordmann, 1837, Hesperus Fauvel, 1874 and Paederomimus Sharp, 1885 (Chani Posse & Ramírez Salamanca in prep.), we examined type material of species belonging to these genera as well as conspecific material from different European and North American collections. Type and non-type material were either examined by MCP during a visit to the Natural History Museum, London, UK (BMNH) or borrowed from the following institutions: Field Museum of Natural History, Chicago, IL, USA (FMNH), Museum für Naturkunde der Humboldt-Universität, Berlin, Germany (ZMHB), Naturhistorisches Museum Wien, Vienna, Austria (NMW), Canadian National Collection of Insects, Ottawa, Canada (CNC) and Snow Entomological Collection, Natural History Museum/Biodiversity Research Center, University of Kansas, Lawrence, USA (SEMC). Based on our revision of relevant material from the abovementioned collections, two new synonyms are here proposed.